2022
DOI: 10.1084/jem.20220202
|View full text |Cite|
|
Sign up to set email alerts
|

Respiratory viral infections in otherwise healthy humans with inherited IRF7 deficiency

Abstract: Autosomal recessive IRF7 deficiency was previously reported in three patients with single critical influenza or COVID-19 pneumonia episodes. The patients’ fibroblasts and plasmacytoid dendritic cells produced no detectable type I and III IFNs, except IFN-β. Having discovered four new patients, we describe the genetic, immunological, and clinical features of seven IRF7-deficient patients from six families and five ancestries. Five were homozygous and two were compound heterozygous for IRF7 variants. Patients ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 74 publications
(141 reference statements)
1
29
0
Order By: Relevance
“…The candidate gene approach-based discovery of AR IFNAR1 and IRF7 deficiencies in four unrelated adults with critical COVID-19 aged 25-50 years who had previously been healthy provided the fundamental information that type I IFN is essential for host defense against SARS-CoV-2, but potentially otherwise redundant in host defense, even over several decades. This redundancy was confirmed not only by reports of other patients with IFNAR1 or IRF7 deficiency (Campbell et al, 2022) but also by the surprising observation of common lossof-function (LOF) alleles of IFNAR1 and IFNAR2 in the Pacific and Arctic regions, respectively (Bastard et al, 2022a;Duncan et al, 2022). Recessive inborn errors of type I IFNs, including XR TLR7 and AR IFNAR1, STAT2, and TYK2 deficiencies, were even found in about 10% of international children hospitalized for COVID-19 pneumonia (Zhang et al, 2022b).…”
Section: Common Monogenic Determinants Of Covid-19mentioning
confidence: 56%
See 3 more Smart Citations
“…The candidate gene approach-based discovery of AR IFNAR1 and IRF7 deficiencies in four unrelated adults with critical COVID-19 aged 25-50 years who had previously been healthy provided the fundamental information that type I IFN is essential for host defense against SARS-CoV-2, but potentially otherwise redundant in host defense, even over several decades. This redundancy was confirmed not only by reports of other patients with IFNAR1 or IRF7 deficiency (Campbell et al, 2022) but also by the surprising observation of common lossof-function (LOF) alleles of IFNAR1 and IFNAR2 in the Pacific and Arctic regions, respectively (Bastard et al, 2022a;Duncan et al, 2022). Recessive inborn errors of type I IFNs, including XR TLR7 and AR IFNAR1, STAT2, and TYK2 deficiencies, were even found in about 10% of international children hospitalized for COVID-19 pneumonia (Zhang et al, 2022b).…”
Section: Common Monogenic Determinants Of Covid-19mentioning
confidence: 56%
“…It was not initially possible to estimate the penetrance of IRF7 and IRF9 deficiencies, as both disorders were described in single patients. A recent study showed that the penetrance of IRF7 deficiency is incomplete ( Campbell et al., 2022 ). STAT1 and STAT2 deficiencies have incomplete penetrance too, suggesting that the penetrance of IRF9 deficiency is also probably incomplete.…”
Section: Rare Monogenic Causes Of Common Infectious Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…She has since remained well with only annual influenza vaccinations and vaccination against COVID-19 for prophylaxis. Two other patients with IRF7 deficiency suffering from severe influenza pneumonia at the ages of 7 mo and 14 yr have recently been reported ( Campbell et al, 2022 ). IRF7 is a transcription factor required for the production of the 17 type I IFNs and three type III IFNs, with IFN-β not being strictly IRF7 dependent in some cell types ( Ciancanelli et al, 2015 ; Zhang et al, 2020b ; Campbell et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%